AGROTOURISM AS A MEANS OF IMPROVING THE ECONOMIC STANDARD OF GUMENG VILLAGE RESIDENTS WITH THE PRINCIPLE OF INTEGRATED FARMING - Maulidia Atna Apsari, Tasya; Ilham Aqsal Mollah, Ramadhan; Irgi Ernistya Purba, Naval; Cahyo Nugroho, Agus; Harsono, Budwi (Journal of Social Comunity Services, 2025)
Objective: Rural tourism presents significant potential for economic diversification and community welfare, particularly through the sustainable utilization of natural and agricultural resources. This study explores the development of integrated farming-based agrotourism in Gumeng Village, Gondang District, as a strategy to enhance local economic growth and village self-sufficiency. Method: A qualitative descriptive approach was employed, utilizing documentation analysis, interviews, direct observations, and secondary data review from village reports and relevant literature. This methodological framework provided a comprehensive understanding of the existing agricultural potential and its integration into tourism development. Results: The findings highlight that Gumeng Village possesses considerable agrotourism potential, particularly in secondary crop cultivation, durian and rambutan plantations, and mountainous camping sites. These resources offer opportunities for structured agrotourism development, contributing to increased Village Original Income (PAD) and fostering economic resilience among the local community. Novelty: This study provides an empirical basis for agrotourism as a driver of rural economic transformation. The findings emphasize the role of agrotourism in promoting village self-sufficiency, encouraging infrastructure development, and supporting policy recommendations for sustainable rural tourism initiatives.